Pulmonary tuberculosis and COVID-19 coinfection: Hickam’s Dictum revisited - Larry Ellee Nyanti; Zhun, Han Wong; Benjamin Sachdev Manjit Singh; Kean, Andrew Wei Chang; Ahmad Tirmizi Jobli; Hock, Hin Chua (Elsevier, 2022)
COVID-19 and pulmonary tuberculosis (PTB) coinfection is associated with increased mortality and presents a unique diagnostic challenge to the clinician. We describe three cases of newly diagnosed PTB in COVID-19 patients treated at our centre and their clinical and radiological features. The challenges associated with diagnosis and management are also explored. Patient 1 was a case of smear positive, endobronchial tuberculosis incidentally diagnosed due to CT changes, and eventually made good recovery. Patient 2 was a case of COVID-19 who succumbed but was diagnosed posthumously due to a positive sputum culture for tuberculosis. Patient 3 showed radiographic features of PTB and was treated empirically for TB. In conclusion, COVID-19 and PTB coinfection should be suspected in the presence of constitutional symptoms, prior immunocompromised states, prolonged respiratory symptoms or fever, or unresolved radiological abnormalities, more so in regions where TB is endemic.